Letter (copy) - Citrine, Walter, 1887-1983
025a-0034-001 INTERNATIONAL. WMC/AC/NS/113. July 10th, 1940, Mr. A. Deakin, Transport & General Workers' Union, Transport House, Smith Square, LONDON S.W.1. Dear Mr. Deakin, Thank you for your letter of 8th July in which you enclose a cheque to the value of £280, being your Union's quota of the £1,000 which the British section of the International Transportworkers' Federation is raising for the assistance of the remaining Spanish seamen in this country. Official receipt is enclosed herewith. Kindly convey to your Executive Council our thanks for their coming forward to help on this occasion. It is very much appreciated and we like you trust the men will soon be on their own feet in suitable employment. Yours Sincerely, General Secretary. Enclosure. 292/946/25a/34